TANGGUNG JAWAB PENDIDIKAN ISLAM - Afrahul Fadhila Daulai (Al-Irsyad: Jurnal Pendidikan dan Konseling, 2017)
The responsibility of Islamic education is not only mandated to individuals, both parents, families, schools, communities and governments but also is the responsibility of faith, morals, physical, resourceful, spiritual and social. This responsibility is basically aimed at guiding, directing and implementing education so that students have faith, have good morals, be healthy physically and spiritually and with their minds can understand the metaphysical trilogy; God, nature and humans. The responsibility of spiritual education is so that people can worship, guide the spirit with a splash of religion and remembrance. While the responsibility of social education is to shape the personality of students and the community so that they have a complete personality and the community has the responsibility to invite people to the path of goodness, compassion and to prevent people from the path of munkar so that an ideal or best society (khairu ummah) is formed.Keywords: Islamic Education, Responsibility